A fluid flow model for the software defined wide area networks analysis - Karol Marszałek; Adam Domański (Scientific Reports)
Abstract The advancement of IT systems necessitates efficient communication methods essential across various sectors, from streaming platforms to cloud-based solutions and Industry 4.0 applications. Enhancing Quality of Service (QoS) in computer networks by focusing on bandwidth and communication delay is critical. Mechanisms like Active Queue Management (AQM) techniques are used, but more advanced solutions are needed to utilize the technological advances in communication technologies. Such advancements are Software-Defined Networks (SDN). Introduced by the SDN decoupling between the control plane and the data plane, it enables advanced real-time traffic shaping and centralized traffic management. This shift allows dynamic routing and improved QoS mechanisms, with research exploring multi-path routing. This paper proposes an extension to the Fluid Flow analysis model for complex networks. This modification allows for the simulation of various networking topologies and can be used to test novel routing and active queue management algorithms in more detail. The obtained numerical analysis demonstrates the model’s advantages over traditional methods, enabling the exploration of new scenarios.